The political economy of internal displacement in Colombia : the case of African palm oil - Loughna, S (2014)
Some 5 million people were classified as internally displaced in Colombia at the end of 2012, which represented about 10 per cent of the population and the highest number in the world at the time. Colombia differs from other countries with high levels of displacement in that it is comparatively politically stable, has effective national institutions, a relatively strong formal economy, and can by no means be described as a ‘failed’ or ‘failing’ state. The displacement literature tends to characterise the phenomenon as a humanitarian crisis and a side effect of the long-running civil war. But Colombians continue to be displaced in very large numbers despite the formal demobilization of the paramilitaries in 2006 and the diminished military capacity and engagement of the guerrillas since about the same period: the same groups that are widely regarded as being the main perpetrators of displacement. This thesis contends that displacement of the civilian population in Colombia is frequently not a consequence of violence, but rather the primary objective, where violence plays a facilitatory role. Moreover, the thesis asserts that these massive levels of displacement are substantively linked to predominantly economically-motivated logics and are regionally specific. By examining an agricultural commodity that has significantly expanded relatively recently in Colombia - African palm oil - this research examines if and how expanded cultivation may be linked to displacement. Using a political economy framework of analysis combined with empirical fieldwork, it explores the ‘localised displacement logics’ whereby land is coercively acquired by powerful local groups. The thesis concludes that the abandonment and dispossession of land from poor and marginalised groups constitutes part of an ongoing process of capitalist expansion and statebuilding in Colombia. Contrary to assertions that it is the intra-state conflict that constitutes the central obstacle to development, Colombia’s current trajectory of capitalist development may actually be a central obstacle to sustainable peace and not lead to an end to displacement.